Confronting the 'Dirty War' in Argentine cinema, 1983-1993 : memory and gender in historical representations - Burucúa, Constanza (Colección Támesis. Monografías, 2009)
The systematic illegal persecution and annihilation of political opponents of the 1979-1983 Argentine military dictatorship, commonly known today as the "Dirty War", became one of the main themes of the nation's cinema after the regime's fall. In this stu